EXTENSION IN THE PEDAGOGY PROGRAM AT UNIEVANGÉLICA (CIPEEX, 2026)
University extension, established as one of the pillars of Brazilian higher education, has been mandatorily integrated into curricula since Resolution CNE/CES No. 7/2018, ensuring students’ participation in practices that articulate teaching, research, and social commitment. This study investigated the impact of extension activities on the training of students in the Pedagogy program at UniEVANGÉLICA, analyzing how these experiences contributed to the development of pedagogical skills and community engagement. The research combined document analysis, literature review, and the study of extension reports, mapping and evaluating the practices developed in the program. The findings confirmed the relevance of extension in the integral training of educators, strengthening the bond between university and community.Keywords: University Extension; Teacher Training; Pedagogy; Community.